The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11136-009-9536-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with health-related quality of life after successful kidney transplantation: a population-based study

Abstract: Among the studied variables, comorbidity and graft function were the main factors associated with the PCSc, and sociodemographic variables and graft function were the main determinants of MCSc. Despite comprehensive, the final regression models explained only a little part of the heath-related quality of life variance. Additional factors, such as personal, environmental and clinical ones might influence quality of life perceived by the patients after kidney transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 52 publications
4
58
0
6
Order By: Relevance
“…Em transplantados renais, os domínios relacionados aos aspectos físicos parecem ser os mais comprometidos (COSTA;NOGUEIRA, 2014;BOHLKE et al, 2009). Estudo mostrou que o componente físico foi influenciado pela presença de comorbidades tais como hipertensão e diabetes, doenças crônicas bastante prevalentes na nossa amostra (BOHLKE et al, 2009).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Em transplantados renais, os domínios relacionados aos aspectos físicos parecem ser os mais comprometidos (COSTA;NOGUEIRA, 2014;BOHLKE et al, 2009). Estudo mostrou que o componente físico foi influenciado pela presença de comorbidades tais como hipertensão e diabetes, doenças crônicas bastante prevalentes na nossa amostra (BOHLKE et al, 2009).…”
Section: Discussionunclassified
“…Estudo mostrou que o componente físico foi influenciado pela presença de comorbidades tais como hipertensão e diabetes, doenças crônicas bastante prevalentes na nossa amostra (BOHLKE et al, 2009). Além disso, outro estudo demonstrou que a QVRS em pacientes transplantados renais com mais de 60 anos foi significativamente inferior em alguns aspectos quando comparado com indivíduos saudáveis, podendo ter contribuído para tal resultado o fato de que a percepção subjetiva da QVRS após o transplante pode permanecer igual porque muitas vezes os pacientes convivem com outras doenças crônicas associadas (CORNELLA et al, 2008).…”
Section: Discussionunclassified
“…(21) Study that assessed health-related QoL issues in 262 renal transplant recipients showed that the physical component was influenced by the presence hypertension and diabetes, factors such as levels of creatinine and hematocrit, that improve after transplantation. (22) The Social elation domain assesses the patient' degree of satisfaction relation to the time spend with family and friends and also the support given by them. This domain showed a sig-nificant increase in the average score after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…(24) The emotional aspects should be considered as important indicators of health and QoL in chronic kidney diseases patients, since the changes in lifestyle imposed by the disease, treatment and progression of symptoms might limit patients' daily activities and also cause negative effects on their perception of QoL. (22,(24)(25)(26) Other studies found that psychological factors tend to improve after transplantation. (21,25) Although the environment domain has presented the lowest scores compared to other QoL domains, it showed significant difference before and after transplantation indicating improvements in this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, patients with higher serum creatinine levels are known to experience poorer physical and psychological outcomes. 12,13 Moreover, the inverse relationship of the adverse effects of immunosuppressive therapy on health-related quality of life of transplant recipients, in both physical and psychological domains, is also welldocumented. 14 Likewise, severe adverse effects of immunosuppressive therapy are known to affect treatment compliance, which in turn adversely affects the patients' physical and psychological well-being.…”
Section: Introductionmentioning
confidence: 99%